Knowledge, attitude and practice towards tuberculosis and the effectiveness of a tuberculosis education program among nurses employed in tuberculosis centers in Libya / Muftah Abdusalam Elbahloul - Muftah Abdusalam, Elbahloul (2020)
Nurses make up by far the largest group of healthcare workers in any part of the world, playing an important role in the direct management of tuberculosis (TB) patients and facing a high risk of infection. Therefore, this study was conducted to explore the knowledge, attitude, and practice towards TB among professional nurses in Libya and the impact of an educational intervention on their knowledge, attitude and practice. A cross-sectional design using self-administered validated questionnaire was conducted to explore the nurses’ KAP towards TB. A total of 384 nurses in tuberculosis centres in Libya participated in the study. TB education intervention was carried out from February to August 2017. A sample of 100 TB nurses was randomly allocated into intervention and control groups. The intervention group received health education regarding tuberculosis using a developed module, while the control group did not receive any education. Knowledge and attitude scores for both groups were evaluated using a self-administered validated questionnaire at baseline, immediate after intervention, three, and six months. Practice score was assessed only at baseline, three, and six months. For the KAP survey, 384 nurses were included. Eighty four (21.9%) were males and 300 (78.1%) were females. Majority of them (85.2%) had low level of knowledge on TB; only 80 (20.8%) had positive attitude towards TB and 326 (84.9%) had unsatisfactory level of practice regarding TB. The knowledge level was found to be significantly associated with age, educational level, work experiences and residence (p = < 0.05). The attitude of nurses towards TB was significantly (p = < 0.05) associated with gender, residence and work experience only. There were significant associations of gender, education level and work experience with practice among the nurses. Knowledge was significantly associated with practice among the nurses towards TB (p <0.001). iv The TB educational intervention program was found to be effective immediately after intervention, as the knowledge score improved by 40.08 (95% CI 41.77, 38.39) (p < 0.001) among the intervention group. The knowledge scores remained stable at 3-month and 6-month follow-up. Likewise, there was significant improvement in attitude score with a mean difference of 1.769 (95% CI 1.88, 1.65) (p < 0.001). The attitude scores remained stable at 3-month and 6-month follow-up. Similarly, there was improvement in practice score with a mean difference of 18.23 (95% CI 16.12, 0.17.43) (p < 0.001). The practice scores remained stable at 6-month follow-up. In Conclusions, most of nurses in tuberculosis centres in Libya had low levels of knowledge, negative attitude and unsatisfactory practice towards TB. Knowledge was found to be associated with practice. The educational intervention carried out was effective in improving the nurses’ knowledge, attitude and practice towards TB over time. Within the control group, there were no significant differences in mean scores of knowledge, attitude and practice over time. There were significant differences in knowledge, attitude and practice scores between intervention and control groups over time (p < 0.001). Key Words: Nurses, Libya, Knowledge, Attitude, Practice, Effectiveness, Tuberculosis